Matricentric Policy Research: Making Room for Mothers in an Inclusive Research Partnership - Turnbull, Lorna A. (Journal of the Motherhood Initiative for Research and Community Involvement, 2019)
In this article, I argue inclusive policy research using "big data" that is informed by matricentric feminist values can yield analysis and recommendations that will be empowering for mothers. Drawing on my experience as a feminist legal scholar and my developing interest in social policy as a means to achieve justice for mothers and other carers, I contend that legal challenges to advance equality for mothers have not been as successful as early assessments might have predicted. Instead, I explore how an inclusive team approach to the kind of social problems that make life difficult for many mothers in Canada could yield better policy that brings them closer to equality. I describe a policy research partnership that includes public servants and community groups as well as academics, informed by an intersectional approach. The partnership will make use of administrative data in Manitoba to explore social policy challenges, including affected community members and public servants from all relevant departments from the outset, ensuring that the questions that are explored reflect the real needs of the people the policies are intended to serve. With two examples of previous research, I illustrate how mother-focused recommendations can flow from the kind of big data available in Manitoba.